Para‐Selective C−H Borylation of Aromatic Quaternary Ammonium and Phosphonium Salts. Issue 21 (21st March 2022) - Lu, Shuo; Zheng, Tianyu; Ma, Jiawei; Deng, Zhangming; Qin, Shengmeng; Chen, Yu; Liang, Yong
Abstract: Aromatic ammonium and phosphonium salts are important synthetic intermediates and multifunctional materials, but para ‐selective functionalization of the aromatic salts remains a challenge. Here we develop an ionic ligand based on our newly designed "biphenyl‐phenanthroline" skeleton and realize the Ir‐catalyzed para ‐selective C−H borylation of seven types of aromatic quaternary ammonium and phosphonium salts. Gram‐scale transformation, late‐stage elaboration for drug molecule, and diversification of borylated products demonstrate the potential utility of this reaction. The mechanistic studies and computational analysis elucidate the origin of para ‐selectivity. Abstract : An anionic sulfamate ligand based on a biphenyl‐phenanthroline skeleton was designed and applied to the para ‐selective C−H borylation of aromatic quaternary ammonium and phosphonium salts. Mechanistic studies and computational analysis elucidated the origin of this unusual selectivity.